RANCANG BANGUN SISTEM INFORMASI PEMESANAN TIKET BUS ONLINE BERBASIS WEB PADA PO. BATANG PANE BARU : Technology, Tickets, Bus, Ordering, WEB. - Nita Maharani Harahap (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2023)
Batang Pane Baru is a business engaged in the field of public transportation. PO. Batang Pane Baru is located on Jalan Sisingamangaraja KM 6.5, Sandpaper Village, Medan Sandpaper District. This company was founded on the eighteenth of March two thousand and two. Purchasing or ordering bus tickets has now shifted from the conventional one, then introduced online via the internet. However, ordering bus tickets is usually done manually by visiting the bus counter. This is because the bus company has not used or utilized information technology as a means of developing services for prospective passengers. System development in this study uses the Laravel Framework. The results of this study are in the form of a proposed website-based ticket booking management information system design, and a proposed website-based ticket booking management information system design that uses UML as a tool in the process of designing a proposed website-based ticket booking management information system.